Architecture: The Art of Integration - Sala, Marco (ICONARCH International Congress of Architecture and Planning, 2014)
Bioclimatic Technologies and sustainable design approach can be applied in the transformation of the natural and built environment at any operational scale. The application of bioclimatic technologies must complete with the conditions of the environment, in relation to the prevalent objectives to be achieved, such reduction of energy consumption, improving both winter and summer comfort, improving visual comfort and natural lighting, indoor comfort and indoor air quality, as well the sustainable use of water resources and the integration of Renewable Energies in buildings. Appropriate building envelope remains the main strategy for sustainable design, but in the mild temperate/mesothermal climates, the rapid changing of outdoor conditions push toward a dynamic response of envelope parameters to allow the maintenance of interior good adaptive comfort. To achieve the reduction of energy consumption both in new and existing buildings, we need the integration among mechanical, architectural and structural approach for a sustainable design approach. Sustainable architecture in Mediterranean area meets its roots in traditional culture and the education of architects and engineers in this part of the world should be aimed to develop a sustainable approach to design, through the understanding of the evolution of the architectural technology and local cultural influences with new models (systems approach, holistic view of the project).